2003
DOI: 10.1055/s-2003-39886
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis of SubstitutedQuinoxalines from New N=N-Polymer-bound 1,2-Diaza-1,3-butadienes

Abstract: The first general protocol for the preparation of different N=N-polymer-bound 1,2-diaza-1,3-butadienes is reported. The utility of these supported reagents in the solid-phase in the preparation of 3-methyl quinoxaline-2-carboxylates by reaction with aromatic 1,2-diamines is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…8 For instance, the Attanasi group utilized azoalkenes as Michael acceptors in various conjugate addition reactions, laying a solid foundation for this field. 9,10 Wang and others demonstrated that in situ generated azoalkenes could serve as heterodienes in copper-catalyzed [4+ n ] reactions. 11 Recently, we and others employed azoalkenes as valuable formal carbon-carbon-nitrogen (CCN) 1,3-dipoles for asymmetric [3+2] reactions.…”
mentioning
confidence: 99%
“…8 For instance, the Attanasi group utilized azoalkenes as Michael acceptors in various conjugate addition reactions, laying a solid foundation for this field. 9,10 Wang and others demonstrated that in situ generated azoalkenes could serve as heterodienes in copper-catalyzed [4+ n ] reactions. 11 Recently, we and others employed azoalkenes as valuable formal carbon-carbon-nitrogen (CCN) 1,3-dipoles for asymmetric [3+2] reactions.…”
mentioning
confidence: 99%